An evaluation of liposome-based diagnostics of pulmonary and extrapulmonary tuberculosis. (3rd May 2020) - Tandel, Nikunj; Joseph, Anish Z; Joshi, Aishwarya; Shrama, Priya; Mishra, Ravi PN; Tyagi, Rajeev K.; Bisen, Prakash S
ABSTRACT: Introduction : Tuberculosis (TB) is still one of the major global health threats and delayed diagnosis or misdiagnosis continues to fuel the global epidemic. The conventional diagnostic approaches have shortcomings that might hinder the process of diagnosis of the disease and ultimately affect the prognosis. Area covered : We emphasize on the process of the synthesis of liposomes, its physicochemical properties affecting the formulation and their utilization in the field of molecular diagnostics for TB. The review also sheds a light on other nanoparticle-based molecular diagnostic approaches for TB. Despite the advent of science, we are yet to have a diagnostic tool that is simple, rapid, sensitive, and specific, and most importantly, one that enables us to demarcate patients with active tuberculosis from those with quiescent lesions, prior vaccination, or other diseases. Expert opinion : The utility of liposomes for diagnostic purposes has been attempted so as to overcome the challenges posed by conventional diagnostic tools for TB. Through this review, we present insights into liposome formulation and selection processes, various studies that report the use of liposome-based diagnostic tools for TB, as well as the limitations associated with the same that can be improvised to make the technology more efficient.